Synthetic, spectroscopic, structural, and electrochemical investigations of ferricenium derivatives with weakly coordinating anions: ion pairing, substituent, and solvent effects. Issue 21 (10th May 2021) - Khan, Firoz Shah Tuglak; Waldbusser, Amy L.; Carrasco, Maria C.; Pourhadi, Hadi; Hematian, Shabnam
Abstract : The effects of ion-pairing, substitution, and media on the redox behavior and ground state electronic structure of a series of ferricenium derivatives are reported. Abstract : A facile and effective strategy for the preparation of a series of ferricenium complexes bearing either electron-donating or electron-withdrawing substituents with weakly coordinating anions such as [B(C6 F5 )4 ] − or SbF6 − is reported. These systems were thoroughly investigated for their ground state electronic structures in both solution and solid states using infrared (IR) and nuclear magnetic resonance (NMR) spectroscopies as well as single crystal X-ray crystallography and electrochemical measurements. The X-ray structures of the six electron-deficient ferricenium derivatives are of particular interest as only a handful (∼5) of such derivatives have been structurally characterized to date. Comparison of the structural data for both neutral and oxidized derivatives reveals that the nature of the substituents on the cyclopentadienyl (Cp) ligands displays a more significant impact on the metal–ligand separations (Fe⋯Ct) in the oxidized species than in their neutral analogs. Our 1 H-NMR measurements corroborate that in the neutral ferrocene derivatives, electron-donating ring substitutions lead to a greater shielding of the ring protons while electron-withdrawing groups via induction deshield the nearby ring protons. However, the data for the paramagnetic ferricenium derivatives reveals that this substitutional behavior is more complex and fundamentally reversed, which is further supported by our structural studies. We ascribe this reversal of behavior in the ferricenium derivatives to the δ back-donation from the iron atom into the Cp rings which can lead to the overall shielding of the ring protons. Interestingly, our NMR results for the electron-deficient ferricenium derivatives in solution also indicate a direct correlation between the solvent dielectric constant and the energy barrier for rotation around the metal–ligand bond in these systems, whereas such a correlation is absent or not significant in the case of the electron-rich ferricenium species or the corresponding neutral ferrocene analogs. In this work, we also present the electrochemical behavior of the corresponding ferricenium/ferrocene redox couples including potential values ( E 1/2 ), peak-to-peak separation (Δ E 1/2 ), and diffusion coefficients ( D ) of the redox active species in order to provide a concise outline of these data in one place. Our electrochemical studies involved three different solvents and two supporting electrolytes. Notably, our findings point to the significant effect of ion-pairing in lowering the energy necessary for reduction of the ferricenium ion and E 1/2 in lower-polarity media. This has significant implications in applications of the ferrocene or ferricenium derivatives as redox agents in low-polarity solvents where an accurate determination of redox potential is critical.